Application of Virtual Reality in the Tourism Industry – a Literature Review - Polishchuk, Elizaveta (Acta Carolus Robertus, 2024)
As we navigate the technological landscape of the 21st century, the emergence of Virtual Tourism (VT) stands as a groundbreaking paradigm in the tourism industry. This article delves into the conceptualization of VT as a distinct type of tourism, addressing prevailing doubts surrounding its technological advancements. Drawing from the varied understanding of VT, ranging from 360-degree videos to immersive Virtual Reality (VR) experiences, we propose the development of a fully immersive multi-sensory setup. This setup aims to engage and stimulate as many human senses as possible to create a close-to-realistic VT encounter.The proposed multi-sensory setup includes the utilization of Head-Mounted Displays (HMDs) for visual and auditory immersion, sensors for smell and taste, gloves embedded with sensors for touch, and temperature-controlled rooms for climate simulation. While the initial investment in such technology may seem substantial, the potential user base for an almost realistic VT experience could outweigh the costs. To validate these propositions, we advocate for an experiment involving a diverse and extensive participant sample. This experiment should encompass individuals from different demographics, health conditions, and perspectives to comprehensively evaluate the acceptance and effectiveness of the multi-sensory VT setup.